I want to know what does it mean by the term including "laplace" word in Laplace Transform
1 回表示 (過去 30 日間)
古いコメントを表示
Esraa Abdelkhaleq
2016 年 5 月 7 日
回答済み: syed ali hasan kibria
2020 年 12 月 15 日
When I tried to solve an eqn analytically using Laplace Transform, the soln included the term laplace(qpl(t), t, s).
I do not know what does this mean?
The commands I entered as following:
>> clear E
>> syms fplc Rc Nc0 Kgr fplh Rh Nh0 Kel real
>> syms qpl(t) s
>> dqpl(t) = diff(qpl(t),t);
>> dqpl(t)= fplc*Rc*Nc0*exp(Kgr*t)+fplh*Rh*Nh0-Kel*qpl(t);
>> L(t)=laplace(dqpl(t),t,s)
L(t) =
(Nh0*Rh*fplh)/s - Kel*laplace(qpl(t), t, s) - (Nc0*Rc*fplc)/(Kgr - s)
採用された回答
Star Strider
2016 年 5 月 7 日
The Symbolic Math Toolbox denotes ‘laplace(qpl(t), t, s)’ as the Laplace transform of the ‘qpl(t)’ function. If you want to denote it in a more traditional form, use the subs function:
L(s) = laplace(dqpl(t),t,s)
L(s) =
(Nh0*Rh*fplh)/s - Kel*laplace(qpl(t), t, s) - (Nc0*Rc*fplc)/(Kgr - s)
L(s) = subs(L(s), {laplace(qpl(t), t, s)}, {QPL(s)})
L(s) =
(Nh0*Rh*fplh)/s - Kel*QPL(s) - (Nc0*Rc*fplc)/(Kgr - s)
This replaces ‘laplace(qpl(t), t, s)’ with ‘QPL(s)’. It is usually good to do this, expecially if you want to simplify your equation or solve for ‘QPL(s)’ later in your code, for example to calculate a transfer function.
8 件のコメント
Star Strider
2016 年 5 月 9 日
For whatever reason, the solve function refuses to solve ‘Laplace_Eqn’ for ‘QPL’ in the commented-out lines.
So, I decided to just directly solve it using the dsolve function:
syms fplc Rc Nc0 Kgr fplh Rh Nh0 Kel qpl(t) s QPL(s) qpl0 real
dqpl(t) = diff(qpl(t),t);
Eqn = dqpl(t) == fplc*Rc*Nc0*exp(Kgr*t)+fplh*Rh*Nh0-Kel*qpl(t);
qpl = dsolve(Eqn, qpl(0) == qpl0);
qpl = simplify(qpl, 'steps', 10)
% Laplace_Eqn = laplace(Eqn);
%
% Laplace_Eqn = subs(Laplace_Eqn, {laplace(qpl(t), t, s)}, {QPL(s)});
%
% Soln = solve(Laplace_Eqn, QPL, 'IgnoreAnalyticConstraints',true, 'IgnoreProperties',true);
The integrated (and simplified) differential equation:
qpl =
(Kel*Nh0*Rh*fplh + Kgr*Nh0*Rh*fplh + Kel*Nc0*Rc*fplc*exp(Kgr*t))/(Kel*(Kel + Kgr)) - exp(-Kel*t)*((Nh0*Rh*fplh)/Kel - qpl0 + (Nc0*Rc*fplc)/(Kel + Kgr))
その他の回答 (1 件)
syed ali hasan kibria
2020 年 12 月 15 日
y¨(t) + 2 ˙y(t) + 10y(t) = 20 cos(6t) y(0) = 1 y˙(0) = 5
0 件のコメント
参考
カテゴリ
Help Center および File Exchange で Calculus についてさらに検索
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!